Experimental research on compressive behavior of seawater and sea sand concrete-filled RPC tubes. (1st November 2020) - Shan, B.; Xu, C.; Lai, D.D.; Xiao, Y.; Li, T.Y.
Highlights: An innovative composite column for being applied in marine engineering, named seawater and sea sand concrete (SWSSC)-filled reactive powder concrete (RPC) tube (SFRPC tube), is presented in the paper. A total of 24 relatively large-scale short columns are tested in axial compression and a special confinement model is proposed for SFRPC tube columns. SFRPC tube system effectively utilizes the ultra-high mechanical properties and excellent corrosion resistance of RPC and fiber reinforced polymer (FRP) as well as combining confinement effect from hoops. Abstract: To address the dilemma of structures constructed with seawater and sea sand concrete (SWSSC), including insufficient durability and high cost, an innovative composite column, named SWSSC-filled reactive powder concrete (RPC) tube (SFRPC tube), is proposed and studied. This hybrid system is composed of a prefabricated RPC thin-wall hollow tube with fiber reinforced polymer (FRP) hoops and infilled SWSSC. In order to understand the basic compressive performance of the proposed composite structure, a total of 24 short columns, with 300 mm outer diameter and 600 mm height, were tested in axial compression. SFRPC tube columns exhibited a multi-crack failure mode on the surface of tube without obvious peeling-off of the RPC cover. The RPC tube can serve as the permanent formwork, and maintain its own integrity in the whole loading process, carrying considerable axial load acting on the composite column, due to its super-high compressive strength. The results reveal that the SFRPC tube system effectively utilizes the ultra-high mechanical properties of RPC and FRP confinement effect. Compressive performance of SFRPC tube columns can be further improved as the volumetric FRP hoop ratio in RPC tube increases. It is found that overlapping joint methods for single FRP hoop in RPC tube and the thickness of RPC tube have no significant effect on the mechanical performance of SFRPC tube columns under the current testing conditions. A special confinement model was also proposed for assessing the axial load carrying capacity of SFRPC tube columns.